The Influence of Corruption Scandals on Government Accountability - Żerkowska-Balas, Marta; Sroka, Anna (Political Preferences, 2019)
The objective of the article is to examine whether corruption scandals involving members of the ruling party lead to changes in support for the government. It will also explore the extent to which the eruption of such scandals and reporting on them leads to an increase in the number of those opposed to the government, and whether in the long run this leads to the activation of the carrot-and-stick mechanism in respect of the governing political party, reflected in increased voting instability during subsequent elections.